2014
DOI: 10.2466/29.25.pms.118k13w1
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits and Exercise Capacity in Male Athletes and Non-Athletes

Abstract: To investigate the relationships between personality traits and athletic capacity, this study compared a sample of 376 young adult men (169 athletes, 207 non-athletes; M age = 23.8 yr., SD = 3.9). 26 lab-based exercise capacity parameters were measured, as well as the Big Five major personality traits using the NEO Five-Factor Inventory. The results indicated that athletes scored higher than non-athletes for Conscientiousness but scores were not statistically different between groups for other personality trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 16 publications
3
44
0
Order By: Relevance
“…We know that the mobility and power of neural processes related to hereditary characteristics [Wang, Lim, Aplin, Chia, McNeill, & Tan, 2008;Milczarek et al, 2009;Malinauskas, Dumciene, Mamkus, & Venckunas, 2014;Sobko, 2015;Sobko, Ulaeva, & Yakovenko, 2016]. However, as evidenced by a number of studies, under the influence of specific training of these qualities can be varied within a limited range for each person.…”
Section: Discussionmentioning
confidence: 99%
“…We know that the mobility and power of neural processes related to hereditary characteristics [Wang, Lim, Aplin, Chia, McNeill, & Tan, 2008;Milczarek et al, 2009;Malinauskas, Dumciene, Mamkus, & Venckunas, 2014;Sobko, 2015;Sobko, Ulaeva, & Yakovenko, 2016]. However, as evidenced by a number of studies, under the influence of specific training of these qualities can be varied within a limited range for each person.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, conscientious behavior likely is important for dedicated athletes or elite athletes. There is some support for this idea-a study found that adult athletes have higher conscientiousness than non-athletes (Malinauskas et al 2014) and more elite athletes have higher levels of conscientiousness than do lowerlevel athletes (Allen et al 2011). The combined evidence is unclear whether conscientiousness and participation in sports are related among adolescents or how this trait and context together predict changes in risky substance use during adolescence.…”
Section: Investigating Activities and Conscientiousnessmentioning
confidence: 99%
“…It concerns, in particular, health related boxing. With such approach program material can and shall be worked out in compliance with individual psycho-physiological characteristics of students (Kokova, Kopylov, 2014) who have different motor functioning levels, different workability and adaptation to physical loads (Siegel, 2009;Okada, 2013;Malinauskas, Dumciene, Mamkus, et al, 2014). In the frames of our research physical fitness is regarded as student's ability to KUZMIN V.A., KOPYLOV Yu.A., KUDRYAVTSEV M.D., TOLSTOPYATOV I.A., GALIMOV G.Y.,…”
Section: Introductionmentioning
confidence: 99%